2023
DOI: 10.1073/pnas.2219029120
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the functional importance and adaptive advantage of A-to-I RNA editing in fungi

Abstract: Adenosine-to-inosine (A-to-I) editing is the most prevalent type of RNA editing in animals, and it occurs in fungi specifically during sexual reproduction. However, it is debatable whether A-to-I RNA editing is adaptive. Deciphering the functional importance of individual editing sites is essential for the mechanistic understanding of the adaptive advantages of RNA editing. Here, by performing gene deletion for 17 genes with conserved missense editing (CME) sites and engineering underedited (ue) and overedited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The editability provides a flexible choice for the organism. Later we will mention that this hypothesis was recently experimentally verified in fungi (Xin et al, 2023).…”
Section: Two Complementary Hypotheses On Adaptive Non-synonymous A-to...mentioning
confidence: 72%
See 2 more Smart Citations
“…The editability provides a flexible choice for the organism. Later we will mention that this hypothesis was recently experimentally verified in fungi (Xin et al, 2023).…”
Section: Two Complementary Hypotheses On Adaptive Non-synonymous A-to...mentioning
confidence: 72%
“…The diversifying hypothesis stresses the flexibility (condition-specificity) of RNA editing (Gommans et al, 2009 ). Apart from the well-acknowledged cases of adaptive recoding in insects (Yu et al, 2016 ; Duan et al, 2017 ) and cephalopods (Garrett and Rosenthal, 2012 ; Liscovitch-Brauer et al, 2017 ) that show temporal-spatial regulation, strong evidence was recently found to support the adaptive proteomic diversification of RNA editing in fungi (Xin et al, 2023 ). The pre-edit allele is beneficial in the asexual stage of Fusarium graminearum while the post-edited allele is beneficial in the sexual stage.…”
Section: Does Non-synonymous Editing In Bacteria Belong To Diversifyi...mentioning
confidence: 99%
See 1 more Smart Citation
“…For justifying the adaptiveness of individual RNA editing sites, a recent research in fungi has taken significant steps towards addressing ‘how the editable state is better than the uneditable state or hardwired G’ by constructing mutant strains [ 22 ]. In the case of a specific A-to-I RNA editing site in Fusarium graminearum , solid observations proved that the genomically uneditable mutant exhibits higher fitness during the asexual stage, while the genomically fixed-G mutant is fitter during the sexual stage.…”
Section: Introductionmentioning
confidence: 99%
“…In PNAS, Xin et al. explore the role of A-to-I editing during sexual development of Fusarium graminearum , a filamentous ascomycete ( 10 ). The authors demonstrate that conserved A-to-I editing sites are functionally important during fungal development and provide evidence that A-to-I editing provides an adaptive advantage.…”
mentioning
confidence: 99%